Photocatalytic degradation of sixteen organic dyes by TiO2/WO3-coated magnetic nanoparticles under simulated visible light and solar light. Issue 1 (February 2018) - Liu, Hualong; Guo, Wang; Li, Yarong; He, Shasha; He, Chiyang
Graphical abstract: Highlights: TiO2 /WO3 -coated magnetic nanocomposite was prepared as a new catalyst. Catalyst rapidly decolorized most of the sixteen dyes under visible light. Catalyst satisfactorily decolorized and mineralized sixteen dyes under sunlight. Catalyst rapidly mineralized the randomly-chosen ten dyes under focused sunlight. Catalyst can be easily recycled by a magnet with a good reusability. Abstract: A type of TiO2 /WO3 -coated magnetic nanoparticles was prepared as catalyst for photodegradation of sixteen organic dyes. The catalyst was characterized by Fourier transform infrared spectroscopy, transmission electron microscopy, X-ray diffraction, vibrating sample magnetometer, and zeta potential analysis. The tested dyes included seven reactive dyes, one metal-complex dye, two base dyes, two direct dyes, and four acidic azo dyes. The photodegradation test showed that, in the presence of catalyst, the degradation rates of dyes were relative to both their chemical structures and adsorption ability. The dyes containing chlorotriazinyl/carbamide group and showing high adsorption ability can be degraded more easily. Most of the tested dyes were degraded rapidly by catalyst under a simulated visible light. Moreover, all the dyes were completely decolorized and satisfactorily mineralized under direct irradiation of solar light. Furthermore, the randomly-chosen ten dyes were completely decolorized and satisfactorily mineralized in a short time of 77–275 min under a focused solar light. In addition, the catalyst can be easily recycled by a magnet with a good reusability. The new catalyst can be potentially utilized as a universal catalyst for degradation of different kind of dyes in water using solar light as an environmentally friendly and low-cost energy resource.